The Impact of Monetary Policy on Financial Performance of Indonesia Commercial Banks: Evidence from Major Challenges during the COVID-19 (The Indonesian Journal of Business Administration, 2021)
This study investigates the impact of Bank Indonesia through its monetary policy response on financial performance of Commercial Banks Group of Business Activities 3 and 4 amid the rising of recent global uncertainty and economic shocks due to COVID-19 outbreak. The sample of this study is in the form of balanced panel data that comprises 33 commercial banks in Indonesia over the period of 2016:1 to 2020:3. To control the effect of the monetary policy responses during the COVID-19 pandemic, this study applied a dummy variable. This study performed a two-step system Generalized Method of Moment (GMM) to achieve the aims of the study. The results show that the lagged dependent variables, monetary policy interest rate, net interest margin, and reserve requirement statistically have a positive impact on bank profitability. The COVID-19 pandemic statistically has an inverse relationship with banks’ performance, it indicates that the occurrence of this virus has disrupted the business of the banks by eroding its financial performance. This study suggested that Bank Indonesia should continue implementing the expansionary monetary policy to maintain the effectiveness of monetary policy transmission in the bank lending channel.Keywords: Monetary Policy, Return on Assets, Return on Equity, COVID-19, Two-step System GMM.